2018
DOI: 10.28991/cej-030974
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of Steel Plate Shear Wall in Multi Span Moment Frame with Various Infill Plate Connection to Column

Abstract: Steel plate shear walls consist of thin infill steel plates attached to beams, called (horizontal boundary elements, HBEs), and columns (vertical boundary elements, VBEs) in structural steel frames. The thin unstiffened web plates are expected to buckle in shear at low load levels and develop tension field action, providing ductility and energy dissipation through tension yielding of the web plate. HBEs are designed for stiffness and strength requirements and are expected to anchor the tension field formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Emeka et al [6] studied the engineering behavior of erodible soil-quarry dust composite at a proportion of 50% quarry dust and 10% cement. The behavior of steel plate shear walls with the various connection of infill plate to columns in multi-span moment frames studied by Raisszadeh et al [7]. The results showed that reducing the infill plate connection to columns will reduce the axial forces in columns.…”
Section: Introductionmentioning
confidence: 99%
“…Emeka et al [6] studied the engineering behavior of erodible soil-quarry dust composite at a proportion of 50% quarry dust and 10% cement. The behavior of steel plate shear walls with the various connection of infill plate to columns in multi-span moment frames studied by Raisszadeh et al [7]. The results showed that reducing the infill plate connection to columns will reduce the axial forces in columns.…”
Section: Introductionmentioning
confidence: 99%
“…50 steel) (Nassernia & Showkati, 2017;Lv et al 2019;Wang et al 2017). LYP is widely used because of having good ductilityand strength in construction and different research Raisszadeh et al, 2018). For instance, they used LYP in the steel shear wall;the results showed that applying this steel can increase absorption energy to63 % and reduce lateral displacement about 16% (Jebelli & Mofid, 2014).…”
Section: Introductionmentioning
confidence: 99%